ACTIVITY BASED COSTING: ANALISIS LITERATUR TENTANG PENGARUHNYA TERHADAP PENENTUAN HARGA JUAL - Revansa, Revansa; Pratama, Muhammad Diko; Sari, Reni Kumala; Nofelisa, Liana; Yuniartie, Emylia (Smart Education, 2025)
Abstract: The purpose of this literature study is to understand the impact of the ABC-based biaya pendekatan on the price of a product in a particular manufacturing company. The research method that is used is the literature study method. The process of gathering, assessing, and analyzing many relevant literary sources—such as scholarly journals and text books—is used in this study in order to gain a comprehensive understanding of the topic being discussed. ABC stands for